Types of parental support systems in youth sports: a literature review and future perspectives - Lavinš, R.; Fernate, A.; Bula-Biteniece, I. (LASE Journal of Sport Science, 2024)
The participation of youth in sports is pivotal for their holistic development, influencing physical health, mental well-being, and social skills. Parents play an indispensable role in this process by providing the necessary financial resources and emotional backing. Their involvement ensures that young people could engage in sports. The aim of the research is to comparatively analyse different parental support systems in youth sport and to establish aims of future research. Research methods: analysis of scientific articles (electronic scientific databases Web of Science Core Collection, Scopus), search keywords - "sport*" OR "youth-sport*" OR "young athlete*" AND "support*" OR "psychological need*" AND "family *" OR "parent*" OR "father*" OR "mother*". The period covered by the research is from 1990 to 2022 and abstracts, conference proceedings, dissertations, book chapters, and articles published in non-peer-reviewed journals were excluded from the search. Main results of the research: the role of parents is considered very important in the athletic development of children and youth, providing emotional, financial, and social support. The research demonstrates that inadequate support from the state/community, coaches and society can hamper parents` ability to effectively support their children and youth in sports.